EFFECT OF BIOFERTILIZER OF FORMULATION DOSE ON INCREASE IN NITRATE ON AQUACULTURE POUNDS ON PEAT SOIL - Ginting, Dicky Efrata; Hasibuan, Saberina; Syafriadiman, Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The research was conducted from August to October 2018 at the Peatland of Kualu Nenas Village, Tambang District, Kampar District, Riau Province. This study aims to determine the effect of formulation biofertilizer doses on increasing Nitrate in peat soil media. The expected benefit in this study is that it can provide fish farmers with scientific information about how best doses of formulated biofertilizer are to increase the productivity of peat soil pools. The method used in this study is the experimental method using a Completely Randomized Design (CRD) of 1 factor with 5 levels of treatment and 4 replications. The treatments used were the administration of formulation biofertilizer with a dose of P1 (700 g/ m2), P2 (750 g / m2), P3 (800 g / m2), P4 (850 g / m2), and P0 (without formulation biofertilizer). The results showed that the dosage formulation biofertilizer with a dose of 750 g / m2 affected the soil quality parameters (total N, total  P,  total  K)  and  water  quality  (pH,   DO,  Temperature,  Nitrate  and Orthopospat). Furthermore, the chemical parameters of water quality during the study were relatively good, temperatures ranged from 25-28 0C, pH ranged from4.4 to 6.8, DO ranged from 3.9 to 7.3, mg / l, Nitrate ranged from 1.58 to 3.23 mg/ l and orthoposphate values range from 2.114 to 8.915 mg / l. The soil quality parameters in the P2 (750 g / m2) N total treatment ranged from 0.25-0.36%, the total P ranged from 21.01 to 89.71%. The total K ranges from 50.92-176.57%. Keyword: Peat Soil, Formulation Biofertilizer, nitrate,